Solitary sclerotic fibroma on the thigh - Kim, Ji Hoon (Arch Craniofac Surg, 2020)
Sclerotic fibroma is a rare fibrous tumor of the skin associated with Cowden’s disease. In 1989, Rapini described sclerotic fibroma without Cowden’s disease as solitary sclerotic fibroma of the skin. It is a solid, well-circumscribed, slow-growing nodular tumor and it looks similar to a keloid scar. Consequently, it is extremely difficult to make a differential diagnosis of solitary sclerotic fibroma with keloid scar based on clinical findings only. The authors report a case of solitary sclerotic fibroma arising at the left lateral thigh of a 25-year-old man.